Human Behavior and Social Environments : a Biopsychosocial Approach. - Saleebey, Dennis (Foundations of social work knowledge., 2012)
Human behavior is a subject so vast that it would seem to defy one's ability to comfortably and confidently grasp its varieties, nuances, shapes, and dynamics. But in this wide-ranging and comprehensive survey of the contexts of human behavior, Dennis Saleebey examines the different social science approaches to understanding the way humans react to and are affected by their environment. Using a biopsychosocial perspective, this book demonstrates that there are many paths of knowledge, many methods of inquiry, and many perspectives that can guide one's understanding of human behavio.